Educational Content Management - Thomas Schmidt and Michael Engelhardt (Ariel, 2005)
In the present paper we discuss aspects and opportunities of educational content management, focusing on structuring and interactivity schemes from semantic notions of components. A transition from standard educational annotations to semantic statements of hyperlinks is discussed. We introduce the Hypermedia Learning Object System hylOs, an online learning system. hylOs is based on a cellular information model, encapsulating content with meta data conforming to the Learning Object Meta data (LOM) standard. Content management is provisioned on this semantic meta data level and allows for variable, dynamically adaptable access structures. Context aware multifunctional links, based on the semantic linking scheme, permit a systematic navigation depending on the learners and didactic needs, thereby exploring the capabilities of the semantic web. hylOs is built upon the more general Multimedia Information Repository (MIR) and the MIR adaptive context linking environment (MIRaCLE), its linking extension. MIR is an open system supporting the standards XML, Corba and JNDI as well as high-level authoring tools for the creation of meta data and WYSIWYG like content editing.